2006
DOI: 10.1021/jf052910b
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Barley and Malt Lipid Transfer Protein 1 (LTP1) toward Heating and Reducing Agents: Relationships with the Brewing Process

Abstract: Barley lipid transfer protein (LTP1) is a heat-stable and protease-resistant albumin that concentrates in beer, where it participates in the formation and stability of beer foam. Whereas the barley LTP1 does not display any foaming properties, the corresponding beer protein is surface-active. Such an improvement is related to glycation by Maillard reactions on malting, acylation on mashing, and structural unfolding on brewing. The structural stability of purified barley and glycated malt LTP1 toward heating ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
81
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 28 publications
12
81
0
7
Order By: Relevance
“…The first consists of a group of proline-rich fragments originating from hordein (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) that are involved in haze formation (14)(15)(16). The second is lipid transfer protein 1 (LTP1; 9.7 kDa in pure form), involved in foam stability (17)(18)(19). The third is protein Z (40 kDa), which appears to have no direct function but may play a role in stabilizing the foam once it is formed (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The first consists of a group of proline-rich fragments originating from hordein (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) that are involved in haze formation (14)(15)(16). The second is lipid transfer protein 1 (LTP1; 9.7 kDa in pure form), involved in foam stability (17)(18)(19). The third is protein Z (40 kDa), which appears to have no direct function but may play a role in stabilizing the foam once it is formed (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Glycation through Maillard reactions, one of the most common types of modifications that happen either in biological or industrial samples, has been observed during malting 130 . Acylation and structural unfolding occurs during mashing and the wort boil 131 . Changes in the physicochemical properties and structure of malt proteins during wort boiling have been investigated by differential scanning calorimetry, SDS-PAGE, two-dimensional electrophoresis, gel filtration chromatography and circular dichroism.…”
Section: Structural Modificationsmentioning
confidence: 99%
“…The ns-LTP1 protein is the second most abundant protein in beer after protein Z. As a protein crucial for many aspects of brewing 31,59 , ns-LTP1 has been particularly well studied with respect to its structural modification during malting and brewing 25,31,108,131 . It constitutes up to 1% of the total malt protein, as monitored by ELISA using a polyclonal antibody developed against native protein 36 .…”
Section: Non-specific Lipid-transfer Proteins (Ns-ltps)mentioning
confidence: 99%
“…The foam promoting forms of ns-LTP1s have an improved amphilicity and adsorption at air-water interfaces of beer 7,87 . Such an improvement is related to glycation via Maillard reactions on malting, acylation on mashing, and structural unfolding on wort boiling 119 . Effects of acylation on ns-LTP1 structure and functional properties have been studied by Pato et al 116 The extent to which denaturation is desirable is limited because the undenatured form of ns-LTP1 has a role in foam stabilization.…”
Section: Ns-ltp1 Role In Beer Foam Formation and Stabilizationmentioning
confidence: 99%